HPPR gene expression in “Salvia sclarea” L. from Republic of Moldova - MARTEA, Rodica; ȘESTACOVA, Tatiana; CLAPCO, Steliana (Studia Universitatis Babeș-Bolyai Biologia, 2015)
Salvia sclarea L. has received attention for its broad range of pharmacological activities and usage in cosmetics industry and food as for fragrances. However, little is known about the genetics of the secondary metabolites synthesis in that plant. In this research, the real-time PCR was used to investigate the expression of HPPR gene involved into acid rosmarinic metabolic pathway. An increased transcriptional activity of gene in hybrids compared to parental forms was identified.